Ecstasy (MDMA): pharmacological and toxic effects, mechanism of action and clinical management (Archives of Clinical Psychiatry, 2008)
BACKGROUND: The consumption of the amphetamine derivative 3,4-methylenedioxymethamphetamine (MDMA, ecstasy) by young people increased in the past years. OBJECTIVES: To conduct a literature review on the pharmacology of MDMA and particularly with respect to the putative mechanism of action implicated in the acute and long-term toxicity and neurotoxic effects. METHODS: A literature review using the key words: 3,4-methylenedioxymethamphetamine, ecstasy, neurotoxicity, intoxication, abuse drugs was performed in the databases MEDLINE and LILACS. The search covered all articles published between 1985 and 2007. RESULTS: There were still many unanswered questions regarding the pharmacology of ecstasy and the pathophysiology of its toxic effects. The fundamental mechanism of action is insufficient to explain all effects induced by the drug. The exact mechanism responsible for mediating the toxic effects of MDMA on 5-HT neurons remain to be elucidated. DISCUSSION: There is limited information in published literature about the underlying pharmacology and mechanism of action that could account for the neurotoxic and other phathophysiological effect of MDMA.